A Molecular characterization of Anaplasma and Ehrlichia microorganisms in bovine populations of the Western Highland Agro-Ecological Zone of Cameroon - Ghislain Roméo NGANGNANG (International Journal of Applied Biology, 2021)
Rickettsial bacteria are important tick-transmitted microorganisms causing disease and death in cattle, sheep, goats and dogs in the area where tick vectors are found, becoming a major problem for improvement of animal production in the endemic areas. The study carried out in the Western Highlands of Cameroon was aimed at highlighting Anaplasma and Ehrlichia species in apparently healthy cattle. A total number of 162 blood samples were collected from cattle and screened via nested-PCR based Reverse Line Blot hybridization (RLB) assay for detection of rickettsial bacteria. Four species of these microorganisms were identified with an overall prevalence of 44.44%, Anaplasma marginale (41.35%) being the most prevalent species followed by Anaplasma sp. ‘Omatjenne’ (15.43%), Anaplasma centrale (8.64%) and Ehrlichia ruminantium (3.08%). Single infection (24.69%) was more frequent among the four types of mix infection observed with a significant difference. Parasite association was most found between A. marginale + Anaplasma sp. ‘Omatjenne’ (11.11%). Female cattle (44.79%) were more infected than males3.93%) but without significant difference while, yearling cattle (50%) were statistically more infected than adults (44.07%). The high prevalence and diversity of rickettsial organisms identified is evidence that disease and their vectors, the Amblyomma and Rhipicephalus (formerly Boophilus) ticks might be widespread in the Western Highlands of Cameroon. However, these findings with veterinary significance suggest the dire need for further research on the presence of other vectors apart from Amblyomma sp. and Rhipicephalus sp. in Cameroon.